Effect of Climate Change on Risk Management Practices in Agriculture in Switzerland - Frei, Samuel (International Journal of Modern Risk Management, 2024)
Purpose: The aim of the study was to examine the effect of climate change on risk management practices in agriculture in Switzerland. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The impact of climate change on risk management practices in Swiss agriculture has become increasingly significant. Farmers in Switzerland are facing heightened risks due to more frequent and severe weather events, such as droughts, floods, and temperature extremes. These changes have led to a greater emphasis on adaptive strategies, including diversified cropping, improved irrigation techniques, and the adoption of climate-resilient crop varieties. Additionally, there is an increased reliance on agricultural insurance and government-supported risk management programs to mitigate financial losses. Unique Contribution to Theory, Practice and Policy: Theory of resilience, adaptive management theory & climate risk management theory may be used to anchor future studies of climate change on risk management practices in agriculture in Switzerland. Practically, there is a need for the development and implementation of tailored risk management strategies that address region-specific challenges and opportunities. Policy frameworks must be updated to support effective climate change adaptation in agriculture. Governments and policy-makers should develop and implement policies that promote the adoption of climate-smart practices and provide financial and technical support to farmers.